Desarrollo motriz y su incidencia en el aprendizaje de los fundamentos técnicos del futbol en niños de 9 - 10 años en el Club Formativo 7 de Junio del cantón Catarama - Campos Guala, Sayeth Alejandra (2023)
Develop the motor skills of 9 and 10-year-old children to facilitate technical fundamentals in soccer, since on many occasions, due to the fact that there are several difficulties for the student to develop their motor and technical skills, it is evident that there is a application deficit. For this, our work will depend on the search for the appropriate methods at our disposal, taking into account that the main problem would be the coach since he is an empirical person who does not know about methodological strategies for correct motor development of children of 9 and 10 years.